(untitled) (Journal of the College of Education for Women, 2022)
The Egyptian labor movement is the oldest trade union movement in the Arab region. Beside, the labor movement in any society is, in fact, only a reflection of the extent of awareness of that class in that society. Such a comparison is based on the degree of social growth the working class has reached. Moreover, the Egyptian working class was characterized by modernity in its inception compared to other social forces and classes. In addition, its development is linked to the level of industrial development of the country. The peasants and craftsmen were the mainstay of production in the Egyptian society over several centuries. The labor union movement also represents the human aspect of the labor force when it encounters and interacts with other social, economic and political forces, meaning that trade unions are the human and popular aspect of economic and political history. Based on the foregoing, the research aims to highlight the main problems and obstacles that faced the labor movement, which was represented by the governmental and party authority with the British colonialism. Based on this, the paper aims to examine the role of labor movement during the Second World War and how it worked to save workers from the economic exploitation and enabled them to obtain their legitimate rights and stand before the capitalists who owned capital. In addition, the Second World War was considered for the working class a psychological school for vocational training and an intellectual school for understanding new principles that the colonialists were working to spread among the Egyptian people during the war period. Accordingly, the researchers adopted the descriptive historical approach scientifically to maintain later the analytical approach. In the light of that, a set of conclusions has reached, such as: The struggle movement of the labor movement is not limited to the workers’ specific demands, but rather extends to struggle for the cause of the homeland (the cause of independence and national liberation).